Še o glagolih premikanja v ruščini in slovenščini - Derganc, Aleksandra (Slavistična revija, 2014)
The article deals with the differences between verbs of motion in Russian and Slovene, particularly with some differences between prefixed verbs with po- derived from the central pairs idti-hodit´ and iti-hoditi.
Keywords: glagol; glagoli premikanja; glagolski vid; Russian; Russian language; ruščina; Slovene; Slovenian langauge; slovenščina; verb; verbs of motion